Towards a source-oriented approach to typological universals - Cristofaro, Sonia (Vilnius University Open Series, 2021)
Typological universals are skewed distributional patterns whereby languages recurrently display certain grammatical patterns as opposed to others. Explanations for these patterns are usually based on their synchronic properties, not actual diachronic processes that shape the pattern cross-linguistically. The paper discusses diachronic evidence about the origins of some typological universals pertaining to word order and aspect/tense conditioned alignment splits. This evidence poses two general challenges for synchronically based explanations of typological universals. First, the relevant patterns do not obviously arise because of the principles postulated to account for these patterns on synchronic grounds. Second, the development of these patterns is a combined result of multiple diachronic processes. These facts point to a new, source-oriented approach to typological universals, one focusing on what source constructions and developmental mechanisms play a role in the shaping of individual patterns, rather than the synchronic properties of the pattern in itself.